2019
DOI: 10.1186/s12862-019-1397-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Bellamya (Mollusca: Gastropoda: Viviparidae) snails on different continents: contrasting patterns of diversification in China and East Africa

Abstract: BackgroundSpecies diversity is determined by both local environmental conditions that control differentiation and extinction and the outcome of large-scale processes that affect migration. The latter primarily comprises climatic change and dynamic landscape alteration. In the past few million years, both Southeast Asia and Eastern Africa experienced drastic climatic and geological oscillations: in Southeast Asia, especially in China, the Tibetan Plateau significantly rose up, and the flow of the Yangtze River … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 99 publications
4
21
0
Order By: Relevance
“…Our molecular dating analysis suggested that the Bellamya lineage in the Pearl River basin diverged from that in India and Thailand approximately 17.12 mya, coinciding with the divergence time (approximately 20 ~ 15 mya) between the Chinese lineage and Africa lineage (Gu et al, ). This timescale correlated with the conclusion of the initial uplift of the QTP during the early Miocene (25 ~ 17 mya; Shi et al, ).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Our molecular dating analysis suggested that the Bellamya lineage in the Pearl River basin diverged from that in India and Thailand approximately 17.12 mya, coinciding with the divergence time (approximately 20 ~ 15 mya) between the Chinese lineage and Africa lineage (Gu et al, ). This timescale correlated with the conclusion of the initial uplift of the QTP during the early Miocene (25 ~ 17 mya; Shi et al, ).…”
Section: Discussionsupporting
confidence: 53%
“…Analyses were run in BEAST v. 1.7.4 (Drummond, Suchard, Xie, & Rambaut, 2012). We used a mutation rate of 1.30% per million years (my), according to Wilke, Schultheiß, and Albrecht (2009) and Gu et al (2019).…”
Section: F I G U R E 1 Sampling Map With Sampling Location Codesmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate how habitat differences (lake endemic or widely distributed) affect shell morphologies of the snails in its evolutionary histories, we compared shell morphology among clades/fossil groups. Based on the phylogenetic relationships of the present study and previous studies, we decided how viviparid species belonged to each clade (Gu et al, 2019;Sengupta et al, 2009;Van Bocxlaer et al, 2018;Zhang et al, 2015). In the fossil species, we mainly focused on presumably lake endemic species (Japan: Igapaludina in the late Pliocene, and Tulotomoides in the late Pliocene-early Pleistocene [Matsuoka, 1985]; Heterogen in the early Pleistocene-present [Matsuoka & Nakamura, 1981;Matsuoka, 1986] we also used a fossil specimen of H. japonica (0.5 Ma: Matsuoka & Nakamura, 1981).…”
Section: Morphological Analyses For All Species and Cladesmentioning
confidence: 99%
“…Molecular phylogenomics using a multilocus approach provides more detailed information than a single or a few genes (Razkin et al, ; Rivers, Darwell, & Althoff, ; Rubinoff & Holland, ; Takahashi & Moreno, ). Although prior studies focusing on phylogenetic relationships among viviparid species were performed using only a few genes (Du et al, ; Gu et al, ; Hirano et al, ; Schultheiß et al, ; Sengupta et al, ; Van Bocxlaer et al, ; Zhang et al, ) or mtDNA genome (Wang, Zhang, Jakovlić, & Wang, ), our previous study indicated that genome‐wide single nucleotide polymorphism (SNP) was more useful for clarifying the relationships and population demographic history between viviparid species (Hirano et al, ).…”
Section: Introductionmentioning
confidence: 99%